Metodología para la enseñanza del derecho penal - Delgado Echeverría, Palmer Stalin; Zhiminaycela Cuenca, Manuel Fernando (Machala, 2020)
The present article has the objective of socializing approaches, theories and proposals that allow an approach to the methodologies for the teaching of Criminal Law, for which anchors and budgets are established that start from the law in general and allow to specify methods and strategies of Criminal law education in accordance with current times, breaking with immobilistic models and projecting towards the learning model, through active methods that lea to the autonomy and active participation of student and meaningful learning. It is based on a qualitative methodological strategy through which a variety of procedures and techniques are used for the collection of information, with a predominance of bibliographic and documentary review, synthetic analytical methods and participant observation, to establish pedagogical analyzes that allow Obtain as a result the socialization of reflections, explanations and arguments about the methodology of law education that can be useful to make the Ecuadorian educational system more efficient.
El presente artículo tiene el objetivo de socializar enfoques, teorías y propuestas que permitan un acercamiento a las metodologías para la enseñanza del Derecho Penal, para lo cual se establecen anclajes y presupuestos que parten del derecho en general y permiten concretar métodos y estrategias de enseñanza del derecho penal acorde con los tiempos actuales, rompiendo con modelos inmovilista y proyectándose hacia el modelo de aprendizaje, mediante métodos activos que conducen a la autonomía y participación activa de los estudiantes y al aprendizaje significativo. El mismo se sustenta en una estrategia metodológica cualitativa mediante la cual se emplea una diversidad de procedimientos y técnicas para la recogida de información, con predominio de la revisión bibliográfica y documental, los métodos analítico sintético y la observación participante, para establecer análisis pedagógicos que permiten obtener como resultado la socialización de reflexiones, explicaciones y argumentaciones sobre la metodología de enseñanza del derecho que puede ser útil para hacer más eficiente el sistema educacional ecuatoriano.
Keywords: DERECHO; HABILIDAD APRENDIZAJE; METODO; ESTRATEGIA